Butein: From ancient traditional remedy to modern nutraceutical. (March 2015) - Semwal, Ruchi Badoni; Semwal, Deepak Kumar; Combrinck, Sandra; Viljoen, Alvaro
Graphical abstract: Highlights: Butein, a natural dietary chalcone, is well-known for its neutraceutical value. The genera Dahlia, Butea, Searsia ( Rhus ) and Coreopsis are common sources of butein. Butein-rich plants are used to treat a range of conditions, most noteably in Asian countries. The anticancer properties of butein have been confirmed through in vivo and in vitro studies. Abstract: Butein (2′, 3, 4, 4′-tetrahydroxychalcone), a simple chalcone derivative, occurs in many unrelated genera including Butea Dahlia, Coreopsis and Searsia. It is a reputed food additive and a common ingredient of botanicals used in herbal medicine formulations, particularly in Asian countries. Although a simple polyphenol, this molecule exhibits a range of pharmacological properties, most notably acting as a potent protein tyrosine kinase inhibitor and as an antineoplastic agent. Researchers have convincingly demonstrated that butein inhibits the epidermal growth factor receptor in HepG2 cells and the tyrosine-specific protein kinase activities of the epidermal growth factor receptor. In addition, it also exhibits promising anti-inflammatory, antidiabetic, antinephritic, antithrombin, anti-angiogenic and hepatoprotective activities in various animal models. Although this molecule is endowed with an impressive list of biological properties, which have acted as scientific support for its commercialization, there are no review articles that coherently discuss various aspects of this chalcanoid. This review aims to explore the pharmacological relevance of butein, together with its structure–activity relationships and mechanisms of action. In addition, the occurrence, chemical synthesis and biosynthesis of butein are discussed.